A Mosquito Psorophora ciliata (Fabricius) (Insecta: Diptera: Culicidae) - Ephraim V. Ragasa; Phillip E. Kaufman (EDIS)
Psorophora ciliata (Fabricius) is a large mosquito that has developed an outsized reputation because of its relatively intimidating heft and persistent biting behavior, including anecdotal historical accounts of its legendary aggressiveness and ‘frightening appearance’. This 6-page fact sheet was written by Ephraim V. Ragasa and Phillip E. Kaufman and published by the UF Department of Entomology and Nematology, October 2012.